PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA QUESTION BOX TERHADAP HASIL BELAJAR IPA KELAS V SD NEGERI 4 PEDAMARAN - Dhena Rabecha Putri; Destiniar; Adrianus Dedy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study intends to determine the effect of the media-assisted teams games tournament (TGT) learning model on the results of learning science in class V SD Negeri 4 Pedamaran and can be expected to increase knowledge about science learning using the media-assisted teams games tournament (TGT) learning model. questionbox. This research is an experimental research. This type of research is quantitative. In this study, researchers used a quasi-experimental design, namely the posttest only control design. The subjects in this study were class V.A and class V.B, which consisted of 36 students. Data collection is done by testing techniques. The data analysis technique uses test questions which are tested for validity and reliability. Based on the results of testing the hypothesis obtained t_count 60.208> t_table 1.698 and a significance value <0.05 (0.000<0.05). So, it can be concluded that the use of the Media Question Box Assisted Teams Games Tournaments (TGT) Learning Model is appropriate for use in learning and has a significant influence.